Preparation method and application of sodium hydroxide-carbon dioxide co-modified charcoal
Through the preparation method of sodium hydroxide-carbon dioxide co-modified biochar, the problem of insufficient catalytic activity of biochar is solved, the removal efficiency of tetracycline is significantly improved, and more efficient environmental governance effect is achieved, and it meets environmental protection and economic requirements.
Patent Information
- Application Number
- CN202411615975.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-07
Smart Images

Figure BDA0005132237770000071 
Figure HDA0005132237880000011 
Figure HDA0005132237880000012
Abstract
Description
Background Art
[0001] The invention relates to a preparation method and application of sodium hydroxide-carbon dioxide co-modified biochar, belonging to the technical field of biochar preparation. Technical Field
[0002] Antibiotics are substances produced by organisms including animals, plants, and microorganisms during their life processes or synthesized by other synthetic methods. The use of low concentrations of antibiotics can inhibit the growth of microorganisms or kill them. Antibiotics play a very important role in the prevention and treatment of diseases caused by infectious bacteria. Antibiotics have now become a common item in people's daily lives and are widely used in the pharmaceutical industry, aquaculture, and agriculture. Antibiotics are produced and used in large quantities by humans, and a large amount of antibiotics must be left in the environment. With the enrichment of organisms, antibiotics will inevitably have a certain impact on organisms in the biosphere. Studies have found that antibiotics remaining in the environment will not only induce the production of drug-resistant bacteria, but also affect the growth and development of organisms. For example, the large-scale use of tetracycline has caused pollution to my country's water environment.
[0003] Tetracycline is a difficult-to-degrade organic substance in nature. Long-term residue in the environment will induce gene mutation, produce resistant microorganisms and resistant genes. Persulfate (PDS) in advanced oxidation technology can produce strong oxidizing active substances under the activation of catalysts, which can efficiently and quickly degrade tetracycline residual in water. The selection of catalysts becomes the key in persulfate technology. Biochar has a wide range of sources, a large specific surface area, and rich surface functional groups. It is the best choice for non-metallic catalysts. Related studies believe that the ratio of C=O (carbonyl oxygen) to CO (hydroxyl oxygen) in biochar can be used as a criterion for the catalytic activity of persulfate. The current direct use of biochar as a catalytic activator is not very effective. Summary of the invention
[0004] In view of the current pollution status of tetracycline, the present invention proposes the environmental protection concept of "treating waste with waste" and provides a new method for adsorbing and degrading tetracycline.
[0005] The present invention provides a preparation method and application of sodium hydroxide-carbon dioxide co-modified biochar. Biochar is prepared using cellulose crystals as raw materials. The biochar is impregnated with a sodium hydroxide solution and then modified at high temperature in a carbon dioxide atmosphere to prepare modified biochar. The modified biochar is applied in the adsorption and degradation of tetracycline. The modified biochar activates persulfate to remove tetracycline in water, and the optimal persulfate dosage and the optimal pH value are explored.
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing sodium hydroxide-carbon dioxide co-modified biochar, the specific steps are as follows:
[0008] (1) thermally cracking cellulose crystal powder under a nitrogen atmosphere to obtain biochar, grinding it and passing it through a 200-mesh sieve to obtain biochar powder, sealing it for later use;
[0009] (2) soaking the biochar powder in a sodium hydroxide solution for a period of time and then filtering and air-drying;
[0010] (3) The air-dried biochar powder is passed through CO2 at high temperature to obtain modified biochar.
[0011] The thermal cracking temperature of step (1) is 450°C-550°C, the time is 2h-3h, the heating rate is 8°C / min-12°C / min; and the nitrogen flow rate is 120mL / min-160mL / min.
[0012] The concentration of the sodium hydroxide solution in step (2) is 1 mol / L-2 mol / L.
[0013] In step (3), the temperature of introducing CO2 at high temperature is 800-950°C, the time is 50-70min, and the flow rate of introducing CO2 is 120mL / min-160mL / min.
[0014] The present invention also provides the use of the modified biochar prepared by the preparation method in the adsorption and degradation of tetracycline. When adsorbing tetracycline, the modified biochar is directly used; when degrading tetracycline, it is used in combination with sodium persulfate, the mass ratio of the modified biochar to the sodium persulfate is 100:10-150, and the reaction pH value is 3-11.
[0015] Beneficial effects of the present invention:
[0016] The biochar of the present invention can effectively improve the surface structure and chemical properties of the biochar through co-modification with sodium hydroxide and carbon dioxide, enhance its adsorption performance, catalytic performance and water treatment capacity, etc., and help to improve the application effect of biochar in environmental governance.
[0017] The present invention adopts sodium hydroxide and carbon dioxide for co-modification reaction, which is more environmentally friendly, avoids toxic chemical reagents that may be used in traditional modification methods, conforms to the concept of green chemistry, and reduces negative impacts on the environment.
[0018] The modified biochar of the present invention has good adsorption performance and high specific surface area, and can be widely used in water treatment, soil improvement, waste treatment and other fields, providing more efficient material support for related industries.
[0019] The biochar raw material in the present invention can be biomass resources such as agricultural waste, which is in line with the development trend of circular economy and helps to efficiently utilize resources and reduce waste.
[0020] The method of sodium hydroxide-carbon dioxide co-modification of biochar of the present invention has significant advantages in environmental protection, economy and application effect, and can promote technological progress in related fields and promote sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 XRD patterns of biochar and modified biochar;
[0022] Figure 2 Raman plots of biochar and modified biochar;
[0023] Figure 3 FTIR images of biochar and modified biochar;
[0024] Figure 4 Persistence radical diagrams for biochar and modified biochar;
[0025] Figure 5 is the adsorption amount of tetracycline by biochar and modified biochar;
[0026] Figure 6 This is an experiment on the adsorption and degradation of tetracycline by biochar and modified biochar;
[0027] Figure 7 The effect of sodium persulfate dosage on the degradation of tetracycline;
[0028] Figure 8 This is the effect of the initial pH value of the solution on the degradation of tetracycline. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific embodiments.
[0030] Example 1
[0031] The preparation method of biochar includes the following specific steps:
[0032] Take 8g of cellulose powder and place it in a quartz crucible, put it into a tubular furnace, introduce nitrogen into the tubular furnace, and the nitrogen flow rate is 120mL / min. After the air in the tubular furnace is exhausted, start heating. Heat to 450℃ for carbonization under a nitrogen atmosphere at a heating rate of 8℃ / min. Stop heating after 3h. After cooling to room temperature, take out the biochar and grind it. After grinding, pass it through a 200-mesh sieve to finally obtain BC450, which is sealed and stored.
[0033] Example 2
[0034] The preparation method of biochar includes the following specific steps:
[0035] Take 8g of cellulose powder and place it in a quartz crucible, put it into a tubular furnace, introduce nitrogen into the tubular furnace, and the nitrogen flow rate is 160mL / min. After the air in the tubular furnace is exhausted, start heating. Heat to 550℃ for carbonization under a nitrogen atmosphere. The heating rate is 12℃ / min. Stop heating after 2h. After cooling to room temperature, take out the biochar and grind it. After grinding, pass it through a 200-mesh sieve to finally obtain BC550, which is sealed and stored.
[0036] Example 3
[0037] The preparation method of biochar includes the following specific steps:
[0038] Take 8g of cellulose powder and place it in a quartz crucible, put it into a tubular furnace, and introduce nitrogen into the tubular furnace with a nitrogen flow rate of 130mL / min. After the air in the tubular furnace is exhausted, start heating. Heat to 500℃ for carbonization under a nitrogen atmosphere with a heating rate of 10℃ / min. Stop heating after 2.5h. After cooling to room temperature, take out the biochar and grind it. After grinding, pass it through a 200-mesh sieve to finally obtain BC500, which is sealed and stored.
[0039] Example 4
[0040] The preparation method of sodium hydroxide-carbon dioxide co-modified biochar, the specific steps are as follows:
[0041] Weigh 8g of biochar BC450 and immerse it completely in 500mL of 1mol / L sodium hydroxide solution, stir and mix, immerse for 28 hours, filter and air-dry;
[0042] Place the air-dried biochar in a quartz crucible, put it into a tubular furnace, and introduce nitrogen gas at a flow rate of 120 mL / min into the tubular furnace. After the air in the tubular furnace is completely removed, start heating. After heating to a specified temperature of 800°C under a nitrogen atmosphere, introduce CO2 gas at a flow rate of 120 mL / min. Keep the temperature for modification for 70 minutes. After the modification is completed, introduce nitrogen again. After cooling to room temperature, take out the modified biochar for grinding. After grinding, pass it through a 200-mesh sieve to obtain the modified biochar and seal it for storage.
[0043] Example 5
[0044] The preparation method of sodium hydroxide-carbon dioxide co-modified biochar, the specific steps are as follows:
[0045] Weigh 8g of biochar BC550 and immerse it completely in 500mL of 1.5mol / L sodium hydroxide solution, stir and mix, immerse for 25 hours, filter and air-dry;
[0046] The air-dried biochar was placed in a quartz crucible, which was then placed in a tubular furnace. Nitrogen gas was introduced into the tubular furnace at a flow rate of 160 mL / min. After the air in the tubular furnace was completely removed, heating began. After heating to a specified temperature of 950°C under a nitrogen atmosphere, CO2 gas was introduced at a flow rate of 160 mL / min. The biochar was kept warm for 60 minutes. After the modification, nitrogen was introduced again. After cooling to room temperature, the modified biochar was taken out for grinding. After grinding, it was sieved through a 200-mesh sieve to obtain the modified biochar, which was sealed and stored.
[0047] Example 6
[0048] The preparation method of sodium hydroxide-carbon dioxide co-modified biochar, the specific steps are as follows:
[0049] Weigh 8 g of biochar BC500 (four portions), immerse them completely in 500 mL of 2 mol / L sodium hydroxide solution, stir and mix, immerse for 24 hours, filter and air-dry;
[0050] The air-dried biochar was placed in a quartz crucible, which was then placed in a tubular furnace. Nitrogen gas was introduced into the tubular furnace at a flow rate of 130 mL / min. After the air in the tubular furnace was completely removed, heating began. After heating to the specified temperatures (800, 850, 900, 950°C) under a nitrogen atmosphere, CO2 gas was introduced at a flow rate of 130 mL / min. The mixture was kept warm for 50 minutes. After the modification, nitrogen was introduced again. After cooling to room temperature, the modified biochar was taken out for grinding. After grinding, it was sieved through a 200-mesh sieve to obtain modified biochars MBC800, MBC850, MBC900, and MBC950, which were sealed and stored.
[0051] Characterization of biochar BC500 and modified biochars MBC800, MBC850, MBC900, and MBC950
[0052] (1) X-ray diffraction analysis (XRD)
[0053] In the experiment, the physical composition of biochar was characterized by X-ray diffractometer. After the dried sample was passed through a 200-mesh sieve, it was scanned at an angle range of 22-90°, a scanning rate of 6° / min, a scanning step of 0.02, and a voltage of 40KV and 40mA. The obtained data was plotted into an XRD diagram to analyze the physical composition of the sample.
[0054] (2) Raman spectroscopy
[0055] Raman spectroscopy is a common method for analyzing substances and their molecular structures. Its principle is to emit light of different frequencies to the surface of the material to form the Raman effect. Because the different molecular structures on the surface of the material can change the distance of the Raman spectrum, various characteristic peaks can be formed, thereby judging the molecular structure of the surface of the material. The surface defect degree of biochar in this experiment was measured by a confocal micro-Raman spectrometer (Xplora Plus, Horiba, France). A laser with a wavelength of 532nm was selected as the emission light source, the laser power was 4-7mW, and the scanning range of the instrument was 0 to 3000cm -1 , select a 50x microscope, the scanning time is 10s, and the number of times is 10.
[0056] (3) Pore size and specific surface area analysis (BET)
[0057] In the experiment, the specific surface area, pore structure and adsorption characteristics of biochar were measured using a specific surface area analyzer. The sample was first degassed in a vacuum environment at 150°C for 2 hours to remove gas and moisture in the sample. Then, nitrogen was fully adsorbed onto the surface of the sample. The sample was then placed in liquid nitrogen for cooling and nitrogen was introduced for adsorption and desorption measurement. Finally, the pore structure was analyzed and the specific surface area was calculated based on the measured data.
[0058] (4) Fourier transform infrared spectroscopy (FTIR)
[0059] The functional groups of biochar were determined by Fourier transform infrared spectroscopy using KBr pellet method at 4 cm -1 Resolution of 400 to 4000 cm -1 Determined by the absorbance.
[0060] (5) Determination of persistent free radicals (EPR)
[0061] About 2 mg of biochar was weighed and placed in a high-purity quartz capillary. The free radical signal of the biochar was detected at room temperature using an electron paramagnetic resonance spectrometer EPR (X-band A300-6 / 1, Bruker, Germany); the scanning time of the instrument was 102.4 s, the time constant was 20.48 ms, the microwave power and frequency were set to 10 mW and 9.88 GHz, respectively, the central magnetic field was 3520 G, the sweep width was set to 400 G, the modulation amplitude and the X-axis resolution were 3 G and 1024 points, respectively.
[0062] Example 7
[0063] Adsorption experiment of tetracycline by biochar and modified biochar
[0064] Take several 250mL conical flasks, add 100mg of biochar BC500, MBC800, MBC850, MBC900, and MBC950 respectively, add 100mL of 20mg / L tetracycline solution, put them into a constant temperature oscillator for oscillation, the oscillation temperature is 25℃, and the oscillation speed is 150r / min. When the oscillation time is 1, 3, 5, 8, 12, 20, 30, 40, 50, and 60min, stop the oscillation, take out 5mL of solution with a liquid dispenser, filter it through a 0.22um filter head and move it into a 10mL glass bottle, detect the absorbance of the solution at 356nm by ultraviolet spectrophotometer, and calculate its concentration by standard curve, and perform two parallel experiments each time.
[0065] Example 8
[0066] Degradation experiment of tetracycline by biochar and modified biochar
[0067] Take several 250mL conical flasks, add 100mg of biochar BC500, MBC800, MBC850, MBC900, and MBC950 respectively, add 100mL of 20mg / L tetracycline solution and 0.1g of sodium persulfate (PDS), put them into a constant temperature oscillator for oscillation, the oscillation temperature is 25℃, the oscillation speed is 150r / min, and the oscillation is stopped when the oscillation time is 8, 20, 40, 60, 90, 120, 180, 240, 300, and 360min. Take out 5mL of solution with a liquid dispenser, quickly mix it with 2.5mL of methanol solution to quench the reaction, filter it through a 0.22um filter head and move it into a 10mL glass bottle, and detect the absorbance of the solution at 356nm by a UV spectrophotometer. Perform two parallel experiments each time.
[0068] Example 9
[0069] Effect of Sodium Persulfate Dosage on Degradation of Tetracycline
[0070] Take multiple 250mL conical flasks, take 100mL of tetracycline solution with an initial concentration of 20mg / L in the conical flask, add 100mg of modified biochar MBC950 and add 0.0125g, 0.025g, 0.05g, 0.1g, and 0.15g of sodium persulfate respectively, put it into a constant temperature oscillator for oscillation, the oscillation temperature is 25℃, the oscillation speed is 150r / min, and the oscillation is stopped when the oscillation time is 8, 20, 40, 60, 90, 120, 180, 240, 300, and 360min. Take out 5mL of the solution with a liquid dispenser, quickly mix it with 2.5mL of methanol solution to quench the reaction, filter it through a 0.22um filter head and move it into a 10mL glass bottle, and detect the absorbance of the solution at 356nm by a UV spectrophotometer. Perform two parallel experiments each time.
[0071] Example 10
[0072] Effect of initial pH value on the degradation of tetracycline
[0073] Take several 250mL conical flasks, take 100mL of tetracycline solution with an initial concentration of 20mg / L in the conical flask, use 0.1mol / L NaOH solution and 0.1mol / L HCL to adjust the initial pH value of the solution to 3.0, 5.0, 7.0, 9.0 and 11.0, add 100mg of MBC950 and 0.05g of sodium persulfate respectively, put it into a constant temperature oscillator and oscillate at a temperature of 25℃. The rotation speed was 150 r / min, and the oscillation was stopped at 8, 20, 40, 60, 90, 120, 180, 240, 300, and 360 min. 5 mL of the solution was taken out with a liquid dispenser, quickly mixed with 2.5 mL of methanol solution to quench the reaction, and filtered through a 0.22 um filter head and transferred into a 10 mL glass bottle. The absorbance of the solution was detected at 356 nm by a UV spectrophotometer, and two parallel experiments were performed each time.
[0074] The XRD patterns of biochar BC500 and modified biochar MBC800, MBC850, MBC900 and MBC950 are as follows: Figure 1As shown in the figure, it can be seen that biochar BC500 and modified biochar MBC800, MBC850, MBC900, MBC950 have obvious peaks at 2θ=23.3°. The broad diffraction peak at 23.3° represents the diffraction peak of graphite carbon (002), indicating that biochar and modified biochar have graphitized structures. In addition, it can be concluded from the figure that biochar BC500 and modified biochar MBC800, MBC850, MBC900, MBC950 have peaks at 2θ=44°, but the peak of BC500 is obviously smaller than that of modified biochar. The diffraction peak at 44° represents the diffraction peak of graphite carbon (100), which shows that the introduction of CO2 at high temperature can promote the formation of graphitized structure of biochar, because the graphitized structure of biochar can enhance the electron transfer ability and help the activation of persulfate, so biochar BC500 and modified biochar can improve the activation efficiency of activated persulfate.
[0075] The Raman spectra of biochar BC500 and modified biochar MBC800, MBC850, MBC900, and MBC950 are shown in Figure 2. Figure 2 As shown in the figure, it can be seen from the data that biochar BC500 and modified biochar MBC800, MBC850, MBC900, MBC950 are at 1343cm -1 and 1597cm -1 There are two characteristic peaks at 1343cm -1 The peak at 1597cm represents the D peak of carbon-based materials. The D peak can reflect the disorder and defect degree of carbon structure. It can be clearly seen in the figure that the D peak of all modified biochars has increased. -1 The peak at represents the G peak of the carbon-based material. The G peak can reflect the vibration amplitude of the sp2 hybridized carbon in the carbon structure. Defects can provide active sites for the catalytic reaction of carbon-based materials. Usually, the degree of defect in biochar materials can be expressed by the intensity ratio of the D peak and the G peak. D / I G The larger the value, the greater the defect of the biochar material. D / I G The value is 0.743, and the I D / I G The value is 0.883, and the I D / I G The value is 0.940, and the I D / I G The value is 0.967, and the I D / I GThe value is 0.976. It can be concluded that when CO2 is introduced to modify biochar, the degree of defect of the final biochar increases with the increase of modification temperature.
[0076] Table 1 shows the data of specific surface area, pore volume and average pore size of biochar BC500 and modified biochar. It can be seen from the data in the table that with the increase of modification temperature, the specific surface area of modified biochar increases. The specific surface area of modified biochar MBC500 is 4.5 times that of biochar BC500, and the pore volume of modified biochar MBC950 is 2.7 times that of biochar BC500. However, the average pore size of modified biochar is smaller than that of biochar BC500. The reason for this phenomenon may be that the temperature is too high, causing partial collapse of the pore structure.
[0077] Table 1 Specific surface area, pore volume and average pore size of biochar and modified biochar
[0078]
[0079] The FTIR spectra of biochar BC500 and modified biochar MBC800, MBC850, MBC900, and MBC950 are shown in Figure 2. Figure 3 As shown in the figure, it can be seen that the FTIR spectra of biochar BC500 and modified biochar MBC800, MBC850, MBC900, and MBC950 are not much different, and the main band number is 1400cm -1 、1591cm -1 、3436cm -1 , 1400cm -1 The representative functional group is CO, 1591cm -1 The representative functional groups are aromatic C=C and C=O, 3436cm -1 The representative functional group is -OH. From the final result in the figure, it can be concluded that the modification of biochar by introducing CO2 at high temperature does not significantly change the oxygen-containing functional groups of biochar.
[0080] The persistent free radical spectra of biochar BC500 and modified biochar MBC800, MBC850, MBC900, and MBC950 are shown in Figure 2. Figure 4As shown, it can be seen from the figure that biochar BC500 has an obvious persistent free radical signal, while the persistent free radical signals of modified biochar MBC800, MBC850, MBC900 and MBC950 have disappeared. From the data shown in the figure, it can be known that the modified biochar causes the persistent free radical signal of biochar to disappear. The persistent free radicals in biochar help activate PDS to produce active free radicals, but the persistent free radicals in the modified biochar disappear, indicating that free radicals do not play a leading role in the process of modified biochar activating PDS, and functional groups, degree of defects and degree of graphitization may play a leading role.
[0081] The adsorption results of tetracycline by biochar BC500 and modified biochar MBC800, MBC850, MBC900 and MBC950 are as follows: Figure 5 As shown in the figure, it can be seen that the adsorption capacity of biochar BC500 for tetracycline is very low, and the adsorption amount at equilibrium is 0.51 mg / g. The adsorption capacity of the modified biochar is enhanced compared with that of biochar BC500. The reason for the increase in adsorption capacity may be that the specific surface area and pore volume of the biochar are improved after modification, providing more sites for the adsorption of tetracycline. Among the modified biochars, MBC950 has the strongest adsorption capacity, with an adsorption amount of 12.54 mg / g at equilibrium, MBC900 has an adsorption amount of 7.89 mg / g at equilibrium, MBC850 has an adsorption amount of 4.45 mg / g at equilibrium, and MBC800 has an adsorption amount of 3.35 mg / g at equilibrium.
[0082] Figure 6The results show the removal effect of tetracycline by using PDS alone and by using biochar or modified biochar / PDS system. It can be seen from the figure that under the experimental conditions of using PDS alone (blank), tetracycline has a degradation effect, but the final degradation efficiency is only 12.8%, which is consistent with the conclusion of the literature. Under the experimental conditions of adding PDS to biochar BC500, the final removal efficiency of tetracycline is 14.2%, which is 1.4% different from the experimental results of using PDS alone, indicating that biochar BC500 has a degradation effect on tetracycline. The activation effect on PDS is very small; among the modified biochars, MBC950 has the best activation performance for PDS, with a tetracycline removal rate of 89.6% at 60 minutes and 91.2% at 360 minutes. The removal rates of tetracycline by other modified biochars MBC900, MBC850, and MBC800 were 65.4%, 38.2%, and 34.5% at 60 minutes, and 84.8%, 66.1%, and 58.8% at 360 minutes, respectively. The degradation effects of MBC800, MBC850, MBC900, MBC950 and BC500 show that the modified biochar has a further improved removal effect on tetracycline, indicating that the modified biochar has a certain activation effect on PDS. The reason why the modified biochar has an activation effect on PDS may be that the graphitization and defect degree of the modified biochar increase, which enhances the transmission efficiency of electrons during activation and increases the activation sites of PDS.
[0083] Figure 7 The results show that the removal effect of modified biochar MBC950 on tetracycline under different experimental conditions of PDS dosage. When the PDS dosage is 0.0125g, 0.025g, and 0.05g (the molar ratio of PDS to tetracycline is 12.5:1, 25:1, and 50:1), the removal rate of tetracycline increases with the increase of PDS dosage. The removal rates are 71.7%, 85.5%, and 93.0% at 360min, respectively. When the PDS dosage is 0.1g (PDS to tetracycline is 12.5:1, 25:1, and 50:1), the removal rate of tetracycline increases with the increase of PDS dosage. When the molar ratio of PDS to tetracycline reached 100:1), the final removal rate was 92.8%; when the dosage of PDS was 0.15g (the molar ratio of PDS to tetracycline reached 150:1), the final removal rate was 93.0%; the experimental results show that when the dosage of PDS was 0.05g, the removal rate of tetracycline by the MBC900 / PDS system has stabilized, and when the modified biochar has been fully utilized, the remaining PDS in the system will not be activated and the removal rate cannot be further improved.
[0084] Figure 8The figure shows the removal effect of tetracycline under the experimental conditions that the modified biochar is MBC950, the PDS dosage is 0.05g, and the pH values are set to 3, 5, 7, 9, and 11 respectively. It can be seen from the figure that with the increase of pH value, the final removal rate of tetracycline has not changed significantly. When pH = 3, the removal rate is 90.2%, when pH = 5, the removal rate is 89.7%, when pH = 7, the removal rate is 89.2%, when pH = 9, the removal rate is 90.7%, and when pH = 11, the removal rate is 89.7%. The experimental results show that the experiment is not sensitive to pH value and has a wide range of adaptable pH values. However, it can be found from the data in the figure that the initial pH of the solution is 11, and the removal rate of tetracycline is higher from 0min to 60min. Some studies believe that the pH of tetracycline ka When the value is less than the pH value, it is favorable for tetracycline to be oxidized. This is because TCH 3+ and TC 2- More easily degraded by free radicals than amphiphilic molecules.
[0085] The present invention uses cellulose powder as raw material to prepare biochar. On the basis of sodium hydroxide impregnation, carbon dioxide is further used to modify the biochar at high temperature. Tetracycline adsorption experiments and degradation experiments of tetracycline by activated persulfate are carried out, and the effects of the optimal persulfate dosage and the initial pH value of the solution on the degradation experiments are explored. It can be seen that the modified biochar MBC950 has the best adsorption effect on tetracycline, and the adsorption amount at equilibrium is 12.54 mg / g. The reason may be that MBC950 has a larger specific surface area and pore volume. After modification, The biochars all had improved abilities to activate persulfate, and MBC950 had the best activation effect on persulfate and the best effect on removing tetracycline. The reason may be that MBC950 carbon material had the best graphitization and carbon defect levels, which were conducive to the activation of persulfate. When the initial concentration of tetracycline was 20 mg / L, the added modified biochar was MBC950, and the solid-liquid ratio was 1 g / L, the optimal dosage of persulfate was 0.5 g / L. The activation of persulfate by modified biochar MBC950 to degrade tetracycline was not sensitive to the pH in the experimental system.
[0086] The specific implementation modes of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing sodium hydroxide-carbon dioxide co-modified biochar, characterized in that: The specific steps are as follows: (1) thermally cracking cellulose crystal powder under a nitrogen atmosphere to obtain biochar, and grinding the biochar and passing it through a 200-mesh sieve to obtain biochar powder; (2) soaking the biochar powder in sodium hydroxide solution and then filtering and air-drying; (3) The air-dried biochar powder is passed through CO2 at high temperature to obtain modified biochar.
2. The method for preparing sodium hydroxide-carbon dioxide co-modified biochar according to claim 1, characterized in that: The thermal cracking temperature of step (1) is 450°C-550°C, the time is 2h-3h, the heating rate is 8°C / min-12°C / min; and the nitrogen flow rate is 120mL / min-160mL / min.
3. The method for preparing sodium hydroxide-carbon dioxide co-modified biochar according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (2) is 1 mol / L-2 mol / L, and the immersion time is more than 24 hours.
4. The method for preparing sodium hydroxide-carbon dioxide co-modified biochar according to claim 1, characterized in that: In step (3), the temperature of introducing CO2 at high temperature is 800-950°C, the time is 50-70min, and the flow rate of introducing CO2 is 120mL / min-160mL / min.
5. Application of the modified biochar prepared by the preparation method of claim 1 in the adsorption and degradation of tetracycline.
6. According to the use described in claim 5, when the modified biochar adsorbs tetracycline, it is used directly; when the modified biochar degrades tetracycline, it is used in combination with sodium persulfate, the mass ratio of the modified biochar to sodium persulfate is 100:10-150, and the pH value of the degradation reaction is 3-11.